Pembentukan Pengajian Di Desa Balimbing Julu Bersama KKN STAIN Madina Kelompok 26 Tahun 2023 - Bagus Pria Alwadipa; Riski Khairani; Muhammad Arif Batubara; Rezky Pramana Putra; Latipah Hanum Batubara; Riska Siregar; Siti Rohani; Ika Yulia Sari; Ayu Wulandari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
STAIN MADINA KKN Group 26 was held in Balimbing Julu Village, Padang Bolak Julu, North Padang Lawas, North Sumatra. The main problem is that in Balimbing Julu Village there are no recitation groups specifically for children or teenagers. In Balimbing Julu Village there is no Madrasah Diniyah Awaliyah (MDA) so children's knowledge about religion is still minimal. In fact, there are still many elementary school children who don't know the hijaiyah letters or short letters. With this recitation, children are more enthusiastic about memorizing short suras, practicing prayer and learning monotheism of the Al-Qur'an.By establishing a study park, children can play while learning religious knowledge. Therefore, as STAIN MADINA KKN students, we collected data by conducting observations and surveys (interviews) with the Balimbing Julu community to hold a recitation garden for children, Friday afternoon recitation for mothers and youth recitation or Naposo Nauli Bulung (NNB) specifically for Friday evenings. 'at the existence of these recitations can strengthen ties between communities.To overcome this problem, we planned to alternately set up a place for recitation at the homes of members of the study group, specifically for children's study gardens, we deliberately held it at the KKN post and the next recitation location was taken over by the chairman of the NNB, namely Maralohot Siregar. With this recitation, it is hoped that it will broaden the knowledge of children, recitation mothers and Naposo Nauli Bulung (NNB). After we established a recitation garden, Friday afternoon recitation for women, and Friday evening recitation for Naposo Nauli Bulung (NNB), we understood that the support of the Balimbing Julu village community had a very important role in realizing these recitation activities. People can learn about the meaning of togetherness, solidarity and kinship.